Institutional Readiness for Implementing Network Technology - Black, Aidan; Derbyshire, Hazel; O’Keefe, Jackie Knowles; Poole, Phil; Riu, Merce Rius; Shen, Jie (Proceedings of the International Conference on Networked Learning, 2000)
Experience from TLTP and FDTL projects increasingly indicates that the institutional change associated with the integration of learning technologies requires leadership, vision and a clear sense of direction from all levels of senior management. The embedding of technologies within an institutional framework is also characterised by a high degree of ownership of that change by the department directly responsible for the teaching (Mayer, 1997). Whilst developments need to meet the immediate needs of staff or departments they should at the same time should be ’ top down’ and demonstrate a clear vision of the role of JCT within the institutions strategic plan.